Helping Behavior among Youth Samples: Does Self-Efficacy, Locus of Control and Demographic Factors Counts? - Okurame, David; Awolola, Oluwakemi; Uye, Emmanuel (Jurnal Ilmu Sosial dan Humaniora, 2025)
The study investigated self-efficacy, locus of control, birth order, family structure and gender on helping behavior among youth samples. Cross-sectional survey research design was adopted while purposive sampling method was used to select four Local Government Areas in Ibadan Greater Municipality (IGM). Data were randomly collected from 225 youths using validated scales and analyzed using t-test of independent mean and Chi square statistics. Five hypotheses were tested and accepted at a p <.05 level of significance. The result revealed that self-efficacy and locus of control influenced helping behavior among study participants in IGM. Furthermore, the result indicated that demographic factors of birth order, family structure and gender significantly influenced helping behavior among study participants. The study concluded that demographic rather than psychological factors were the major significant factors that influence helping behavior among youths in IGM. It is recommended that government and non-governmental organizations should design programmes that would change the attitudes of youths towards helping others.